2021
DOI: 10.1038/s42003-021-02859-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poor sleep on the immune cell landscape as assessed by single-cell analysis

Abstract: Poor sleep has become an important public health issue. With loss of sleep durations, poor sleep has been linked to the increased risks for diseases. Here we employed mass cytometry and single-cell RNA sequencing to obtain a comprehensive human immune cells landscape in the context of poor sleep, which was analyzed in the context of subset composition, gene signatures, enriched pathways, transcriptional regulatory networks, and intercellular interactions. Participants subjected to staying up had increased T an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 74 publications
1
31
0
Order By: Relevance
“…In a recent study, authors analyzed with mass cytometry and single-cell RNA sequencing the characteristics of peripheral blood mononuclear cells obtained from healthy subjects sleep-deprived. They found expansion of T lymphocytes and plasma cells, increase of autoimmunity markers and altered subsets of myeloid cells, confirming the relationship between sleep alteration and immune dysregulation/chronic subclinical inflammation [ 74 ].…”
Section: Sleep Deprivation Immune System and Viral Infectionsmentioning
confidence: 75%
“…In a recent study, authors analyzed with mass cytometry and single-cell RNA sequencing the characteristics of peripheral blood mononuclear cells obtained from healthy subjects sleep-deprived. They found expansion of T lymphocytes and plasma cells, increase of autoimmunity markers and altered subsets of myeloid cells, confirming the relationship between sleep alteration and immune dysregulation/chronic subclinical inflammation [ 74 ].…”
Section: Sleep Deprivation Immune System and Viral Infectionsmentioning
confidence: 75%
“…Blood was collected from six healthy individuals before and after 24-h sleep deprivation (preSU and postSU, respectively) and then subsequently analyzed using mass cytometry by time of flight (CyTOF) and single-cell RNA sequencing (scRNA-seq). Coincident with the aforementioned studies, Liu et al (2021) found increases in circulating T cells (TC) as well as decreases in myeloid cells (MYE) postSU as assessed by classical lineage markers using scRNA-seq. Next, the five major immune cell lineages (TC, NK, BC, MC, and DC) were further sub-clustered into transcriptionally distinct subsets.…”
Section: Sleep Disruption-induced Changes To Systemic Physiologymentioning
confidence: 57%
“…These approaches are required to garner critical information on the molecular and cellular interactions underpinning sleep disruption associated malignancies. A study by Liu et al (2021) provide unique insight into the dynamic single-cell alterations underlying sleep disruption-induced rewiring of the immune cell landscape. Blood was collected from six healthy individuals before and after 24-h sleep deprivation (preSU and postSU, respectively) and then subsequently analyzed using mass cytometry by time of flight (CyTOF) and single-cell RNA sequencing (scRNA-seq).…”
Section: Sleep Disruption-induced Changes To Systemic Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Rhythmical biological regulation of the immune system is mediated by intricate crosstalk between the nervous and endocrine systems [ 70 72 ]. Dysregulation of sleep–wake cycles, like prolonged sleep deprivation, disrupts the immune system, resulting in increased rates of viral infection and weak antigen processing and antibody formation [ 70 , 73 , 74 ].…”
Section: The Interplay Between Sleep–wake Cycles and Cancermentioning
confidence: 99%